2016
DOI: 10.21053/ceo.2015.01487
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cochlear Implant Outcomes in Patients With Prelingual Deafness

Abstract: Objectives.To evaluate the factors that limit post-cochlear implantation (CI) speech perception in prelingually deaf children.Methods.Patients with CI were divided into two groups according to Category of Auditory Performance (CAP) scores 3 years post-CI: the poor performance group (poor performance group, CAP scores≤4, n=41) and the good performance group (good performance group, CAP scores≥5, n=85). The distribution and contribution of the potential limiting factors related to post-CI speech perception was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Although BCNC stenosis or atresia is used to diagnose CND, BCNC width was not significantly correlated with ECAP responses in our study, indicating that it cannot be used to predict the degree of CND. Several previous studies have reported worse CI outcomes among patients with BCNC stenosis than among patients with a normal BCNC, while these studies performed group comparisons between patients with BCNC stenosis (BCNC width <1.5 or 1.4 mm) and other groups (such as patients with a BCNC width >1.5 mm) (Kang et al, 2016 , 2019 ; Chung et al, 2018 ). However, almost all participants in our study had BCNC.…”
Section: Discussionmentioning
confidence: 99%
“…Although BCNC stenosis or atresia is used to diagnose CND, BCNC width was not significantly correlated with ECAP responses in our study, indicating that it cannot be used to predict the degree of CND. Several previous studies have reported worse CI outcomes among patients with BCNC stenosis than among patients with a normal BCNC, while these studies performed group comparisons between patients with BCNC stenosis (BCNC width <1.5 or 1.4 mm) and other groups (such as patients with a BCNC width >1.5 mm) (Kang et al, 2016 , 2019 ; Chung et al, 2018 ). However, almost all participants in our study had BCNC.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive evaluation of prognostic factors enables CI team to counsel the CI candidates for the post-CI outcome accurately. It was known that the physiologic factors (age at CI, duration of deafness, meningitis, genetic mutation), the anatomical factors (inner ear anomaly, BCNC, CND), functional factors (residual hearing level, preoperative use of hearing aid), device factors (coding strategy, brand of CI, the percentage of active electrode), and education/rehabilitation factors (mode of communication, socioeconomic status, post-CI rehabilitation service, family support) could be related to the CI outcome [ 22 ]. In this current study, BCNC, CND, and the duration of hearing aids use were related to post-CI outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1989, when USA Food and Drug Administration approved cochlear implants for children, this technology has developed so fast that today cochlear implantation (CI) is the treatment of choice for children diagnosed with sever-to-profound hearing loss in majority of developed countries (13). Numerous trials demonstrated advantages of CI: improved hearing, speech perception, and language development (47).…”
Section: Introductionmentioning
confidence: 99%